Low-temperature-resistant PET (Polyethylene Terephthalate) coiled material as well as preparation method and application thereof
By using specific melted ethylene-methyl acrylate copolymer, maleic anhydride graft copolymer and temperature-resistance enhancement filler in PET coils, the problem of PET coils becoming brittle and frozen in low-temperature environments is solved, and the problem of PET coils becoming brittle and frozen in low-temperature environments is realized. Higher low temperature and heat resistance.
Patent Information
- Application Number
- CN202411740819.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-18
AI Technical Summary
Existing PET coils are prone to become brittle and frozen in low-temperature environments, and cannot meet the continuous use needs in low-temperature environments.
The specific melting finger ethylene-methyl acrylate copolymer is used as the toughening agent, and maleic anhydride grafted styrene-ethylene-butadiene-styrene copolymer is used as the compatibilizer, and carbon nanotubes and vinyl tri- The temperature-resistance reinforcement filler produced by reacting ethoxysilane with polyether modified polysiloxane ensures that each component is fully dispersed and compatible.
It significantly improves the low-temperature and heat resistance of PET coils, making them less likely to become brittle and cracked at low temperatures, and increases the thermal deformation temperature and adapts to a wider temperature range.
Smart Images

Figure BDA0005162569380000131 
Figure BDA0005162569380000141
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a low-temperature resistant PET coil and a preparation method and application thereof. Background Art
[0002] PET, or polyethylene terephthalate, is a commonly used plastic material. PET has good mechanical properties, its impact strength is 3-5 times that of other films, and it has good folding resistance. PET has excellent chemical resistance and can withstand oil, fat, dilute acid and dilute alkali, and has high resistance to most solvents. PET has low water vapor permeability and good barrier properties, which can effectively prevent the penetration of gas, water, oil and odor. PET is non-toxic, odorless, hygienic and safe, and has high transparency, can effectively block ultraviolet rays, has good gloss and beautiful appearance. These characteristics make PET coils an ideal packaging material, which is widely used in many fields such as food, beverages, and electronic devices.
[0003] Although PET coils can adapt to a wider temperature range than other plastics, they will still become brittle and even crack after long-term use in low-temperature environments, and cannot meet the needs of continuous use in these low-temperature environments. In order to further improve the low-temperature resistance of PET coils, various methods have been adopted in the prior art, for example: by adding plasticizers such as phthalates, epoxy soybean oil, rubber toughening agents, etc., the flexibility and fluidity of the PET molecular chain can be increased, thereby improving its low-temperature resistance; by blending PET with other polymers such as polyethylene (PE), polypropylene (PP), etc., the low-temperature resistance of PET can be improved; by adding nanofillers such as carbon nanotubes, nanosilica, etc., the low-temperature resistance of PET can be improved; by surface modification methods such as plasma treatment, chemical plating, etc., the performance of the PET surface can be improved to improve its low-temperature resistance.
[0004] The above methods can improve the low temperature resistance of PET coils to a certain extent, but there are also certain limitations. For example, the addition of plasticizers may cause the material to precipitate easily at high temperatures, affecting the long-term stability and appearance of the material; the compatibility of the blended materials in the blending modification is poor, and phase separation is easy to occur, affecting the uniformity and mechanical properties of the material; the nanofiller has poor dispersibility and is easy to agglomerate, affecting the uniformity and processing performance of the material; surface modification can only improve the performance of the material surface, and has limited improvement on the low temperature resistance of the entire material, and the processing process is complicated and the cost is high. Therefore, there is an urgent need for a low temperature resistant PET coil with excellent comprehensive performance. Summary of the invention
[0005] The purpose of the present invention is to provide a low-temperature resistant PET coil, which adopts ethylene-methyl acrylate copolymer with a specific melt index as a toughening agent and maleic anhydride grafted styrene-ethylene-butadiene-styrene copolymer as a compatibilizer, so that various components in a base material are fully dispersed and compatible, and a heat-resistant reinforcing filler is added to further improve the heat resistance of the material, so that the PET coil not only has good mechanical properties, but also does not have the problems of brittleness and cracking at low temperatures.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] The present invention provides a low-temperature resistant PET coil, comprising the following raw materials:
[0008] PET, ethylene-methyl acrylate copolymer, heat-resistant reinforcing filler, maleic anhydride grafted styrene-ethylene-butadiene-styrene copolymer, nucleating agent, antioxidant, lubricant.
[0009] Preferably, the low temperature resistant PET coil comprises the following raw materials in parts by weight:
[0010] 170-200 parts by weight of PET, 12-15 parts by weight of ethylene-methyl acrylate copolymer, 8-12 parts by weight of heat-resistant reinforcing filler, 5-8 parts by weight of maleic anhydride grafted styrene-ethylene-butadiene-styrene copolymer, 3-5 parts by weight of nucleating agent, 1-2 parts by weight of antioxidant, and 2-4 parts by weight of lubricant.
[0011] Preferably, the method for preparing the temperature-resistant reinforcing filler comprises the following steps:
[0012] 35-40 parts by weight of octamethylcyclotetrasiloxane, 4-6 parts by weight of tetra-sec-butoxysilane, 0.2-0.4 parts by weight of aminoethylaminoisobutylmethyldimethoxysilane, 0.03-0.05 parts by weight of sodium lauryl sulfate, 0.05-0.08 parts by weight of potassium hydroxide and 2-4 parts by weight of water are mixed, stirred for reaction, and cooled to obtain an amino-containing polysiloxane;
[0013] 10-15 parts by weight of amino-containing polysiloxane, 2.5-5 parts by weight of epoxy-terminated allyl polyether, 0.01-0.03 parts by weight of stannous octoate and 90-100 parts by weight of dimethyl sulfoxide are mixed, stirred for reaction, and concentrated under reduced pressure to obtain polyether-modified polysiloxane;
[0014] 10-15 parts by weight of carbon nanotubes, 0.2-0.5 parts by weight of vinyl triethoxysilane and 90-100 parts by weight of acetone are mixed and stirred, and then 1-4 parts by weight of polyether modified polysiloxane is added and stirred continuously. After centrifugation, the mixture is washed and dried to obtain a heat-resistant reinforcing filler.
[0015] The invention adds ethylene-methyl acrylate copolymer with a specific melt index as a toughening agent, maleic anhydride grafted styrene-ethylene-butadiene-styrene copolymer as a compatibilizer and a nucleating agent, so that various components in the base material are fully dispersed and compatible, thereby ensuring that the PET coil has good mechanical properties and dimensional stability.
[0016] In order to improve the temperature resistance of PET coils, the present invention adopts a temperature-resistant reinforcing filler prepared with carbon nanotubes, vinyl triethoxysilane and polyether modified polysiloxane as raw materials, so that the PET coil can still maintain good mechanical strength and toughness in a low temperature environment, and will not have problems such as brittleness and cracking. At the same time, the heat deformation temperature is also improved to a certain extent. The adaptability of the PET coil is wider, and it can be used for low-temperature refrigeration and high-temperature sterilization without deformation.
[0017] In the preparation process of the heat-resistant reinforcing filler, octamethylcyclotetrasiloxane, tetra-sec-butoxysilane and aminoethylaminoisobutylmethyldimethoxysilane are first reacted to obtain amino-containing polysiloxane, and then the epoxy group of the terminal epoxy allyl polyether is reacted with the amino group of the amino-containing polysiloxane to graft the allyl polyether with a fatty long chain structure onto the polysiloxane to obtain polyether-modified polysiloxane, and finally, the carbon nanotubes treated with vinyltriethoxysilane and the polyether-modified polysiloxane are cross-linked to obtain the heat-resistant reinforcing filler.
[0018] The addition of temperature-resistant reinforcing fillers significantly improves the low-temperature resistance and heat resistance of PET coils. Moreover, it has good dispersion in the matrix and will not agglomerate. At the same time, it has good compatibility with PET, which can ensure the stable performance of the coils. Among them, the polyether segments in polyether-modified polysiloxanes have long flexible carbon chains. These long-chain structures enhance the flexibility and toughness of the material. At low temperatures, the flexible segments can absorb and disperse external stresses, prevent the material from becoming brittle and cracking, thereby improving the low-temperature resistance of PET coils; the high bond energy and long bond length of the silicon-oxygen bond enable polysiloxane to maintain a stable structure at low temperatures, prevent the material from becoming brittle and cracking, and further improve the low-temperature resistance; the polyether segments and polysilane branched segments in polyether-modified polysiloxanes can form a local network structure, which can effectively disperse and absorb external stresses, improve the toughness and low-temperature resistance of the material; in low-temperature environments, the high strength and high modulus of carbon nanotubes can effectively transmit and disperse external stresses, improve the toughness and impact resistance of the material, and prevent the material from becoming brittle and cracking; carbon nanotubes It can also act as an auxiliary nucleating agent, promote the crystallization process of PET, improve the crystallinity of the material, make PET more stable at low temperatures and less prone to embrittlement; in a high temperature environment, the cross-linked structure of carbon nanotubes and polyether-modified polysiloxane can form an efficient heat conduction network, help quickly dissipate heat, prevent local overheating, and improve the thermal stability of the material; the polysiloxane, polyether segment and carbon nanotube in the temperature-resistant reinforcing filler form a multiphase composite structure in the PET matrix, and this multiphase structure can effectively disperse and absorb external stress and improve the overall performance of the material, including heat resistance and mechanical strength; the polyether segment and silicon oxygen segment in the polyether-modified polysiloxane have good compatibility with the PET matrix, and can form a stable interface layer, which improves the compatibility and interface bonding strength of the material, which helps to improve the comprehensive performance of the material.
[0019] Furthermore, the method for preparing the heat-resistant reinforced filler comprises the following steps:
[0020] 35-40 parts by weight of octamethylcyclotetrasiloxane, 4-6 parts by weight of tetra-sec-butoxysilane, 0.2-0.4 parts by weight of aminoethylaminoisobutylmethyldimethoxysilane, 0.03-0.05 parts by weight of sodium lauryl sulfate, 0.05-0.08 parts by weight of potassium hydroxide and 2-4 parts by weight of water are mixed, stirred at 130-150° C. and 80-100 rpm for reaction for 4.5-6 hours, and cooled to room temperature to obtain amino-containing polysiloxane;
[0021] Mix 10-15 parts by weight of amino-containing polysiloxane, 2.5-5 parts by weight of epoxy-terminated allyl polyether, 0.01-0.03 parts by weight of stannous octoate and 90-100 parts by weight of dimethyl sulfoxide, stir and react at 75-80° C. and 80-100 rpm for 7-10 hours, and concentrate under reduced pressure to recover the solvent to obtain polyether-modified polysiloxane;
[0022] 10-15 parts by weight of carbon nanotubes, 0.2-0.5 parts by weight of vinyl triethoxysilane and 90-100 parts by weight of acetone are mixed, stirred at room temperature and 80-100 rpm for 3-5 hours, then 1-4 parts by weight of polyether modified polysiloxane are added and stirred for 4-6 hours, centrifuged, washed and dried to obtain a heat-resistant reinforcing filler.
[0023] Preferably, the carbon nanotubes are single-walled carbon nanotubes with a tube diameter of 1-5 nm and a length of 20-50 μm.
[0024] Preferably, the melt index of the olefin-methyl acrylate copolymer is 2-5 g / 10 min, measured at 190° C. according to the method in ASTM D1238.
[0025] The present invention also found that the ethylene-methyl acrylate copolymer with a melt index of 2-5g / 10min at 190°C / 2.16kg can better cooperate with the heat-resistant reinforcing filler, and improve the toughness of the material while ensuring the low-temperature impact resistance. This is because the methyl acrylate group can form weak interactions such as hydrogen bonds with the ester group in PET, enhance the interfacial bonding force, have a better matching degree within this range, help to form a stable phase interface, and improve compatibility; and moderate fluidity helps to refine the particles of the dispersed phase, so that the ethylene-methyl acrylate copolymer and the heat-resistant reinforcing filler form a uniform microstructure in the PET matrix, effectively improving the comprehensive performance of the material.
[0026] Preferably, the nucleating agent is at least one of nano calcium carbonate, nano silicon dioxide, talcum powder, sepiolite, montmorillonite and carbon nanotubes.
[0027] Furthermore, the nucleating agent is a mixture of nano calcium carbonate and nano silicon dioxide in a weight ratio of 10:3-5.
[0028] Preferably, the antioxidant is at least one of antioxidant DLTDP, antioxidant DSTDP, antioxidant 264, antioxidant 616, and antioxidant 2246.
[0029] Furthermore, the antioxidant is a mixture of antioxidant DLTDP and antioxidant 264 in a weight ratio of 2-3:5.
[0030] Preferably, the lubricant is at least one of N,N′-ethylene bisstearamide, pentaerythritol stearate, stearic acid amide, polyethylene glycol, and silicone powder.
[0031] Preferably, the lubricant is a mixture of N,N′-ethylene bisstearamide and pentaerythritol stearate in a weight ratio of 1:1-2.
[0032] Preferably, the particle size of the nano calcium carbonate is 40-80 nm.
[0033] Preferably, the particle size of the nano-silicon dioxide is 30-60 nm.
[0034] The present invention provides a method for preparing a low-temperature resistant PET coil, comprising the following steps:
[0035] According to the raw material formula, PET, ethylene-methyl acrylate copolymer, heat-resistant reinforcing filler, maleic anhydride grafted styrene-ethylene-butadiene-styrene copolymer, nucleating agent, antioxidant and lubricant are weighed, the weighed raw materials are added into a high-speed mixer and mixed for 15-20 minutes at a stirring speed of 250-300 rpm, and then added into an extruder and extruded at an extrusion temperature of 275-280° C. and a screw speed of 50-60 rpm, and finally the low-temperature resistant PET coil is obtained through calendering, pulling, cutting and winding processes.
[0036] Application of the above low-temperature resistant PET coil in the preparation of packaging materials.
[0037] The applications include but are not limited to dumpling packaging boxes, raw meat packaging boxes, lunch boxes, trays, and cup lids.
[0038] Compared with the prior art, the advantages and beneficial effects of the present invention are:
[0039] 1. The present invention provides a method for preparing a low-temperature resistant PET coil, by adding a heat-resistant reinforcing filler prepared by reacting carbon nanotubes, vinyl triethoxysilane and polyether modified polysiloxane, and using an ethylene-methyl acrylate copolymer with a specific melt index as a toughening agent, and a maleic anhydride grafted styrene-ethylene-butadiene-styrene copolymer as a compatibilizer, the comprehensive performance of the PET coil is further improved, so that the PET coil not only has good mechanical properties, but also does not have the problem of brittleness and cracking at low temperatures.
[0040] 2. The addition of the heat-resistant reinforcing filler of the present invention significantly improves the low-temperature resistance and heat resistance of the PET coil, and it has good dispersibility in the matrix without agglomeration, and at the same time has good compatibility with PET, which can ensure the stable performance of the coil; the heat-resistant reinforcing filler is obtained by cross-linking carbon nanotubes and polyether-modified polysiloxane, and the polyether segment in the polyether-modified polysiloxane has a relatively long flexible carbon chain. At low temperatures, the flexible segment can absorb and disperse external stress to prevent the material from becoming brittle and cracking, and the polyether segment and polysilane branch segment in the polyether-modified polysiloxane can form a local network structure, which can effectively disperse and absorb external stress and improve the toughness and low-temperature resistance of the material.
[0041] 3. The present invention selects ethylene-methyl acrylate copolymer with a melt index of 2-5 g / 10 min at 190°C / 2.16 kg. Within this range, it has a better matching degree, helps to form a stable phase interface, improves compatibility, and moderate fluidity helps to refine the particles of the dispersed phase, so that the ethylene-methyl acrylate copolymer and the heat-resistant reinforcing filler form a uniform microstructure in the PET matrix, effectively improving the comprehensive performance of the material. DETAILED DESCRIPTION
[0042] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0043] PET, brand: FR530NC010, melt index is 6cm 3 / 10min (280℃, 2.16kg, ISO1133), Manufacturer: DuPont, USA.
[0044] Ethylene-methyl acrylate copolymer Ⅰ, EMA, brand: AC1224, melt index is 2g / 10min (190℃, 2.16kg, ASTM D1238), acrylic acid content is 24%, manufacturer: Dow Chemical Company, USA.
[0045] Ethylene-methyl acrylate copolymer II, EMA, brand: Optema TM TC 220, melt index is 5g / 10min (190℃, 2.16kg, ASTM D1238), acrylic acid content is 24%, manufacturer: ExxonMobil Corporation, USA.
[0046] Ethylene-methyl acrylate copolymer III, EMA, brand: AC1125, melt index is 0.5g / 10min (190℃, 2.16kg, ASTM D1238), acrylic acid content is 25%, manufacturer: Dow Chemical Company, USA.
[0047] Ethylene-methyl acrylate copolymer IV, EMA, brand: AC12024, melt index is 20g / 10min (190℃, 2.16kg, ASTM D1238), acrylic acid content is 24%, manufacturer: Dow Chemical Company, USA.
[0048] Maleic anhydride grafted styrene-ethylene-butadiene-styrene copolymer, SEBS-g-MAH, melt index is 3g / 10min (190°C, 2.16kg, ISO1133), and the grafting rate is 2%.
[0049] Epoxy-terminated allyl polyether, model: KL-11B, average molecular weight 500, epoxy value 0.17eq / 100g, manufacturer: Liaoning Kelong Fine Chemical Company.
[0050] Example 1
[0051] This embodiment provides a low-temperature resistant PET coil, comprising the following raw materials in parts by weight:
[0052] 170 parts by weight of PET, 12 parts by weight of ethylene-methyl acrylate copolymer I, 8 parts by weight of heat-resistant reinforcing filler, 5 parts by weight of maleic anhydride grafted styrene-ethylene-butadiene-styrene copolymer, 3 parts by weight of nucleating agent, 1 part by weight of antioxidant, and 2 parts by weight of lubricant.
[0053] The nucleating agent is a mixture of nano calcium carbonate and nano silicon dioxide in a weight ratio of 10:3.
[0054] The antioxidant is a mixture of antioxidant DLTDP and antioxidant 264 in a weight ratio of 2:5.
[0055] The lubricant is a mixture of N,N′-ethylene bisstearamide and pentaerythritol stearate in a weight ratio of 1:2.
[0056] The preparation method of the temperature-resistant reinforced filler comprises the following steps:
[0057] 35 parts by weight of octamethylcyclotetrasiloxane, 4 parts by weight of tetra-sec-butoxysilane, 0.2 parts by weight of aminoethylaminoisobutylmethyldimethoxysilane (CAS: 23410-40-4), 0.03 parts by weight of sodium lauryl sulfate, 0.05 parts by weight of potassium hydroxide and 2 parts by weight of water were mixed, stirred at 130° C. and 80 rpm for 4.5 hours, and cooled to room temperature to obtain an amino-containing polysiloxane;
[0058] 10 parts by weight of amino-containing polysiloxane, 2.5 parts by weight of epoxy-terminated allyl polyether, 0.01 parts by weight of stannous octoate and 90 parts by weight of dimethyl sulfoxide were mixed, stirred at 75° C. and 80 rpm for 7 hours, and concentrated under reduced pressure to recover the solvent to obtain a polyether-modified polysiloxane;
[0059] 10 parts by weight of carbon nanotubes, 0.2 parts by weight of vinyl triethoxysilane and 90 parts by weight of acetone are mixed, stirred at room temperature and 80 rpm for 3 hours, then 2.5 parts by weight of polyether modified polysiloxane are added and stirred for 4 hours, washed and dried after centrifugation to obtain a heat-resistant reinforcing filler; the carbon nanotubes are single-walled carbon nanotubes with a tube diameter of 1-5 nm and a length of 20-50 μm.
[0060] This embodiment provides a method for preparing a low-temperature resistant PET coil, comprising the following steps:
[0061] According to the raw material formula, PET, ethylene-methyl acrylate copolymer I, heat-resistant reinforcing filler, maleic anhydride grafted styrene-ethylene-butadiene-styrene copolymer, nucleating agent, antioxidant and lubricant are weighed, and the weighed raw materials are added to a high-speed mixer and mixed for 15 minutes at a stirring speed of 250 rpm, and then added to an extruder for extrusion molding at an extrusion temperature of 275°C and a screw speed of 50 rpm, and finally through calendering, pulling, cutting and winding processes, the low-temperature resistant PET coil is obtained.
[0062] Example 2
[0063] This embodiment provides a low-temperature resistant PET coil, comprising the following raw materials in parts by weight:
[0064] 200 parts by weight of PET, 15 parts by weight of ethylene-methyl acrylate copolymer I, 12 parts by weight of heat-resistant reinforcing filler, 8 parts by weight of maleic anhydride grafted styrene-ethylene-butadiene-styrene copolymer, 5 parts by weight of nucleating agent, 2 parts by weight of antioxidant, and 4 parts by weight of lubricant.
[0065] The nucleating agent is a mixture of nano calcium carbonate and nano silicon dioxide in a weight ratio of 10:5.
[0066] The antioxidant is a mixture of antioxidant DLTDP and antioxidant 264 in a weight ratio of 3:5.
[0067] The lubricant is a mixture of N,N′-ethylene bisstearamide and pentaerythritol stearate in a weight ratio of 1:1.
[0068] The preparation method of the temperature-resistant reinforcing filler is the same as that of Example 1.
[0069] This embodiment provides a method for preparing a low-temperature resistant PET coil, comprising the following steps:
[0070] According to the raw material formula, PET, ethylene-methyl acrylate copolymer I, heat-resistant reinforcing filler, maleic anhydride grafted styrene-ethylene-butadiene-styrene copolymer, nucleating agent, antioxidant and lubricant are weighed, and the weighed raw materials are added to a high-speed mixer and mixed for 20 minutes at a stirring speed of 300 rpm, and then added to an extruder for extrusion molding at an extrusion temperature of 280°C and a screw speed of 60 rpm, and finally through calendering, pulling, cutting and winding processes, the low-temperature resistant PET coil is obtained.
[0071] Example 3
[0072] This embodiment provides a low-temperature resistant PET coil, comprising the following raw materials in parts by weight:
[0073] 170 parts by weight of PET, 12 parts by weight of ethylene-methyl acrylate copolymer II, 8 parts by weight of heat-resistant reinforcing filler, 5 parts by weight of maleic anhydride grafted styrene-ethylene-butadiene-styrene copolymer, 3 parts by weight of nucleating agent, 1 part by weight of antioxidant, and 2 parts by weight of lubricant.
[0074] The nucleating agent is a mixture of nano calcium carbonate and nano silicon dioxide in a weight ratio of 10:3.
[0075] The antioxidant is a mixture of antioxidant DLTDP and antioxidant 264 in a weight ratio of 2:5.
[0076] The lubricant is a mixture of N,N′-ethylene bisstearamide and pentaerythritol stearate in a weight ratio of 1:2.
[0077] The preparation method of the temperature-resistant reinforcing filler is the same as that of Example 1.
[0078] This embodiment provides a method for preparing a low-temperature resistant PET coil, comprising the following steps:
[0079] According to the raw material formula, PET, ethylene-methyl acrylate copolymer II, heat-resistant reinforcing filler, maleic anhydride grafted styrene-ethylene-butadiene-styrene copolymer, nucleating agent, antioxidant and lubricant are weighed, the weighed raw materials are added into a high-speed mixer and mixed for 15 minutes at a stirring speed of 250 rpm, and then added into an extruder and extruded at an extrusion temperature of 275°C and a screw speed of 50 rpm. Finally, the low-temperature resistant PET coil is obtained through calendering, pulling, cutting and winding processes.
[0080] Comparative Example 1
[0081] The difference between this comparative example and Example 1 is that in the raw material of the low-temperature resistant PET coil, ethylene-methyl acrylate copolymer I is replaced by ethylene-methyl acrylate copolymer III.
[0082] Comparative Example 2
[0083] The difference between this comparative example and Example 1 is that in the raw material of the low-temperature resistant PET coil, ethylene-methyl acrylate copolymer I is replaced by ethylene-methyl acrylate copolymer IV.
[0084] Comparative Example 3
[0085] The difference between this comparative example and Example 1 is that the preparation method of the heat-resistant reinforcing filler is different, which is as follows: The preparation method of the heat-resistant reinforcing filler comprises the following steps:
[0086] 35 parts by weight of octamethylcyclotetrasiloxane, 4 parts by weight of tetra-sec-butoxysilane, 0.2 parts by weight of aminoethylaminoisobutylmethyldimethoxysilane (CAS: 23410-40-4), 0.03 parts by weight of sodium lauryl sulfate, 0.05 parts by weight of potassium hydroxide and 2 parts by weight of water were mixed, stirred at 130° C. and 80 rpm for 4.5 hours, and cooled to room temperature to obtain an amino-containing polysiloxane;
[0087] 10 parts by weight of carbon nanotubes, 0.2 parts by weight of vinyl triethoxysilane and 90 parts by weight of acetone are mixed, stirred at room temperature and 80 rpm for 3 hours, then 2.5 parts by weight of amino-containing polysiloxane are added and stirring is continued for 4 hours. After centrifugation, the mixture is washed and dried to obtain a heat-resistant reinforcing filler; the carbon nanotubes are single-walled carbon nanotubes with a tube diameter of 1-5 nm and a length of 20-50 μm.
[0088] Comparative Example 4
[0089] The difference between this comparative example and Example 1 is that the preparation method of the heat-resistant reinforcing filler is different, which is as follows: The preparation method of the heat-resistant reinforcing filler comprises the following steps:
[0090] 10 parts by weight of commercially available polysiloxane, 2.5 parts by weight of epoxy-terminated allyl polyether, 0.01 parts by weight of stannous octoate and 90 parts by weight of dimethyl sulfoxide were mixed, stirred at 75°C and 80 rpm for 7 hours, and concentrated under reduced pressure to recover the solvent to obtain polyether-modified polysiloxane; the commercially available polysiloxane was dimethyl silicone oil with a viscosity of 500 mPa.s (25°C);
[0091] 10 parts by weight of carbon nanotubes, 0.2 parts by weight of vinyl triethoxysilane and 90 parts by weight of acetone are mixed, stirred at room temperature and 80 rpm for 3 hours, then 2.5 parts by weight of polyether modified polysiloxane are added and stirred for 4 hours, washed and dried after centrifugation to obtain a heat-resistant reinforcing filler; the carbon nanotubes are single-walled carbon nanotubes with a tube diameter of 1-5 nm and a length of 20-50 μm.
[0092] Comparative Example 5
[0093] The difference between this comparative example and Example 1 is that the preparation method of the heat-resistant reinforcing filler is different, which is as follows: The preparation method of the heat-resistant reinforcing filler comprises the following steps:
[0094] 10 parts by weight of carbon nanotubes, 0.2 parts by weight of vinyl triethoxysilane and 90 parts by weight of acetone are mixed, stirred at room temperature and 80 rpm for 3 hours, then 2.5 parts by weight of commercially available polysiloxane are added and stirring is continued for 4 hours. After centrifugation, the mixture is washed and dried to obtain a heat-resistant reinforcing filler; the commercially available polysiloxane is dimethyl silicone oil with a viscosity of 500 mPa.s (25°C); the carbon nanotubes are single-walled carbon nanotubes with a diameter of 1-5 nm and a length of 20-50 μm.
[0095] Comparative Example 6
[0096] The difference between this comparative example and Example 1 is that the preparation method of the heat-resistant reinforcing filler is different, which is as follows: The preparation method of the heat-resistant reinforcing filler comprises the following steps:
[0097] 35 parts by weight of octamethylcyclotetrasiloxane, 4 parts by weight of tetra-sec-butoxysilane, 0.2 parts by weight of 3-aminopropyltrimethoxysilane, 0.03 parts by weight of sodium lauryl sulfate, 0.05 parts by weight of potassium hydroxide and 2 parts by weight of water were mixed, stirred at 130° C. and 80 rpm for 4.5 hours, and cooled to room temperature to obtain amino-containing polysiloxane;
[0098] 10 parts by weight of amino-containing polysiloxane, 2.5 parts by weight of epoxy-terminated allyl polyether, 0.01 parts by weight of stannous octoate and 90 parts by weight of dimethyl sulfoxide were mixed, stirred at 75° C. and 80 rpm for 7 hours, and concentrated under reduced pressure to recover the solvent to obtain a polyether-modified polysiloxane;
[0099] 10 parts by weight of carbon nanotubes, 0.2 parts by weight of vinyl triethoxysilane and 90 parts by weight of acetone are mixed, stirred at room temperature and 80 rpm for 3 hours, then 2.5 parts by weight of polyether modified polysiloxane are added and stirred for 4 hours, washed and dried after centrifugation to obtain a heat-resistant reinforcing filler; the carbon nanotubes are single-walled carbon nanotubes with a tube diameter of 1-5 nm and a length of 20-50 μm.
[0100] Performance Testing
[0101] 1. According to the standard GB / T 1843-2008, the impact strength of the low-temperature resistant PET coils prepared in the above Examples 1-3 and Comparative Examples 1-6 was tested, and the impact strength was measured at the initial stage, after being placed at -60°C for 2 months, and after being placed at -120°C for 2 months. Five groups were tested in parallel, and the average value was taken. The results are shown in Table 1.
[0102] Table 1. Impact strength test results
[0103]
[0104]
[0105] 2. According to the standard ISO75-2-2013, the heat deformation temperature of the low temperature resistant PET coils prepared in the above Examples 1-3 and Comparative Examples 3-6 was tested, Method A: 1.8 MPa, 10 groups were paralleled, and the average value was taken. The results are shown in Table 2.
[0106] Table 2. Heat deformation temperature test results
[0107] Heat deformation temperature / ℃ Example 1 239 Example 2 236 Example 3 237 Comparative Example 3 228 Comparative Example 4 230 Comparative Example 5 227 Comparative Example 6 233
[0108] It can be seen from the above performance test results that the PET coils prepared in Examples 1-3 have excellent impact resistance, low temperature resistance and heat deformation resistance, especially the comprehensive performance of the PET coil in Example 1 is the most outstanding. This is because the present invention adopts a homemade temperature-resistant reinforcing filler and an ethylene-methyl acrylate copolymer with a specific melt index as a toughening agent, which significantly improves the low temperature resistance and heat resistance of the PET coil, and it has good dispersibility in the matrix and will not agglomerate. At the same time, it has good compatibility with PET, which can ensure the stable performance of the coil.
[0109] In comparison, since Comparative Examples 1-6 did not adopt the necessary technical solutions, they were significantly worse than Examples 1-3 in the corresponding performance tests. In Comparative Examples 1-2, ethylene-methyl acrylate copolymer with a specific melt index was not used as a toughening agent, and in Comparative Examples 3-6, no temperature-resistant reinforcing filler prepared by a specific method was used. From the results, it can be seen that the impact resistance, low temperature resistance and heat deformation temperature of the PET coil were reduced. The above experimental results further prove the importance of the technical solution defined in the present invention for its technical effect.
[0110] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A low temperature resistant PET coil, characterized in that: It includes the following raw materials in parts by weight: 170-200 parts by weight of PET, 12-15 parts by weight of ethylene-methyl acrylate copolymer, 8-12 parts by weight of heat-resistant reinforcing filler, 5-8 parts by weight of maleic anhydride grafted styrene-ethylene-butadiene-styrene copolymer, 3-5 parts by weight of nucleating agent, 1-2 parts by weight of antioxidant, and 2-4 parts by weight of lubricant; the heat-resistant reinforcing filler is prepared by reacting carbon nanotubes, vinyl triethoxysilane and polyether modified polysiloxane.
2. The low temperature resistant PET coil according to claim 1, characterized in that: The preparation method of the temperature-resistant reinforced filler comprises the following steps: 35-40 parts by weight of octamethylcyclotetrasiloxane, 4-6 parts by weight of tetra-sec-butoxysilane, 0.2-0.4 parts by weight of aminoethylaminoisobutylmethyldimethoxysilane, 0.03-0.05 parts by weight of sodium lauryl sulfate, 0.05-0.08 parts by weight of potassium hydroxide and 2-4 parts by weight of water are mixed, stirred for reaction, and cooled to obtain an amino-containing polysiloxane; 10-15 parts by weight of amino-containing polysiloxane, 2.5-5 parts by weight of epoxy-terminated allyl polyether, 0.01-0.03 parts by weight of stannous octoate and 90-100 parts by weight of dimethyl sulfoxide are mixed, stirred for reaction, and concentrated under reduced pressure to obtain polyether-modified polysiloxane; 10-15 parts by weight of carbon nanotubes, 0.2-0.5 parts by weight of vinyl triethoxysilane and 90-100 parts by weight of acetone are mixed and stirred, and then 1-4 parts by weight of polyether modified polysiloxane is added and stirred continuously. After centrifugation, the mixture is washed and dried to obtain a heat-resistant reinforcing filler.
3. The low temperature resistant PET coil according to claim 2, characterized in that: The preparation method of the temperature-resistant reinforced filler comprises the following steps: 35-40 parts by weight of octamethylcyclotetrasiloxane, 4-6 parts by weight of tetra-sec-butoxysilane, 0.2-0.4 parts by weight of aminoethylaminoisobutylmethyldimethoxysilane, 0.03-0.05 parts by weight of sodium lauryl sulfate, 0.05-0.08 parts by weight of potassium hydroxide and 2-4 parts by weight of water are mixed, stirred at 130-150° C. and 80-100 rpm for reaction for 4.5-6 hours, and cooled to room temperature to obtain amino-containing polysiloxane; Mix 10-15 parts by weight of amino-containing polysiloxane, 2.5-5 parts by weight of epoxy-terminated allyl polyether, 0.01-0.03 parts by weight of stannous octoate and 90-100 parts by weight of dimethyl sulfoxide, stir and react at 75-80° C. and 80-100 rpm for 7-10 hours, and concentrate under reduced pressure to recover the solvent to obtain polyether-modified polysiloxane; 10-15 parts by weight of carbon nanotubes, 0.2-0.5 parts by weight of vinyl triethoxysilane and 90-100 parts by weight of acetone are mixed, stirred at room temperature and 80-100 rpm for 3-5 hours, then 1-4 parts by weight of polyether modified polysiloxane are added and stirred for 4-6 hours, centrifuged, washed and dried to obtain a heat-resistant reinforcing filler.
4. The low temperature resistant PET coil according to claim 1, characterized in that: The melt index of the olefin-methyl acrylate copolymer is 2-5 g / 10 min as measured at 190° C. and 2.16 kg according to ASTM D1238.
5. The low temperature resistant PET coil according to claim 1, characterized in that: The nucleating agent is at least one of nano calcium carbonate, nano silicon dioxide, talcum powder, sepiolite, montmorillonite and carbon nanotubes.
6. The low temperature resistant PET coil according to claim 5, characterized in that: The nucleating agent is a mixture of nano calcium carbonate and nano silicon dioxide in a weight ratio of 10:3-5.
7. The low temperature resistant PET coil according to claim 1, characterized in that: The antioxidant is a mixture of antioxidant DLTDP and antioxidant 264 in a weight ratio of 2-3:
5.
8. The low temperature resistant PET coil according to claim 1, characterized in that: The lubricant is a mixture of N,N'-ethylene bisstearamide and pentaerythritol stearate in a weight ratio of 1:1-2.
9. The method for preparing a low temperature resistant PET coil according to any one of claims 1 to 8, characterized in that: The steps include: According to the raw material formula, PET, ethylene-methyl acrylate copolymer, heat-resistant reinforcing filler, maleic anhydride grafted styrene-ethylene-butadiene-styrene copolymer, nucleating agent, antioxidant and lubricant are weighed, the weighed raw materials are added into a high-speed mixer for mixing, and then added into an extruder for extrusion molding, and finally the low-temperature resistant PET coil is obtained through calendering, pulling, cutting and winding processes.
10. Use of the low-temperature resistant PET coil according to any one of claims 1 to 8 in the preparation of packaging materials.